2018
DOI: 10.3847/1538-3881/aae68d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Tomography. II. A Second Method for Mapping the Velocity Field of the Milky Way Interstellar Medium and a Comparison with Spiral Structure Models

Abstract: In this work, we derive a spatially resolved map of the line-of-sight velocity of the interstellar medium and use it, along with a second map of line-of-sight velocity from Paper I of this series, to determine the nature of gaseous spiral structure in the Milky Way. This map is derived from measurements of the 1.527 µm diffuse interstellar band (DIB) in stellar spectra from the APOGEE survey and covers the nearest 4-5 kpc of the Northern Galactic plane. We cross-check this new DIB-based line-of-sight velocity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…The studies of Pettitt et al (2014Pettitt et al ( , 2015 found that fewer grand-design discs tend to allow the more irregular emission features in the observed l3map to be matched to observations. Other authors have made similar findings, with many outer arm features (> 4) needed to reproduce the observations (Li et al 2016) with the time evolution of features such as the Perseus arm, pointing towards a dynamic kind of nature (Tchernyshyov et al 2018;Baba et al 2018). Stellar material has also become even more usable for studies of Galactic arms, with transient spiral features also pro-D. Colombo, A. Duarte-Cabral, A. R. Pettitt et al: SEDIGISM spiral arms viding a good match to observed stellar velocities (Grand et al 2015;Sellwood et al 2019).…”
Section: Discussion: the Milky Way A Grand-design Or Flocculent Spiral Galaxy?supporting
confidence: 66%
“…The studies of Pettitt et al (2014Pettitt et al ( , 2015 found that fewer grand-design discs tend to allow the more irregular emission features in the observed l3map to be matched to observations. Other authors have made similar findings, with many outer arm features (> 4) needed to reproduce the observations (Li et al 2016) with the time evolution of features such as the Perseus arm, pointing towards a dynamic kind of nature (Tchernyshyov et al 2018;Baba et al 2018). Stellar material has also become even more usable for studies of Galactic arms, with transient spiral features also pro-D. Colombo, A. Duarte-Cabral, A. R. Pettitt et al: SEDIGISM spiral arms viding a good match to observed stellar velocities (Grand et al 2015;Sellwood et al 2019).…”
Section: Discussion: the Milky Way A Grand-design Or Flocculent Spiral Galaxy?supporting
confidence: 66%
“…Thus, they are the result of perturbations induced by current spiral structures according to Siebert et al (2012). However, it is noted that they assume a steady spiral structure in their simulation, while the origin of the spiral structures is far from clear (Baba et al 2018;Tchernyshyov et al 2018;Sellwood et al 2018). Therefore, our results may not clearly exclude the perturbation of spiral arms originated from other mechanism but only rule out a steady density wave spiral structure.…”
Section: Discussionmentioning
confidence: 97%
“…Another compelling result of our analysis is the variation in filament orientations along the l and v LSR corresponding to the Perseus and Outer spiral arms. If the filamentary structures are L4, page 4 of 8 bone-like feature of the spiral arms, as could be the case for some GMFs (Goodman et al 2014), these variations are potential indications that segments of the spiral arm are being disrupted (Tchernyshyov et al 2018). While one could expect alignment of the GMF at the spiral shock, the observations may correspond to features farther downstream, which could be torqued into misalignments by the action of turbulence in the spiral arm (see, for example, Kim et al 2006).…”
Section: Discussionmentioning
confidence: 99%